2/7 (x-3)= 1/4 [x-2/3+4]

### 1 Answer | Add Yours

We want to solve for x in:

`(2/7)*(x-3) = (1/4)*[x - 2/3 + 4]`

First, let's simplify the expression inside the bracket by getting:

`-2/3 + 4 = -2/3 + 12/3 = 10/3`

Hence, we have:

`(2/7)*(x-3) = (1/4)*(x + 10/3)`

`(2*(x-3))/7 = (x + 10/3)/4`

`(2x - 6)/7 = (x+10/3)/4`

Then, we cross-multiply:

`4*(2x-6) = 7*(x + 10/3)`

`8x - 24 = 7x + 70/3`

` ` `8x - 7x = 70/3 + 24`

`x = 70/3 + 72/3 = 142/3 = 47 1/3`

Hence, x = `47 1/3`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes